The Nature of the Implied Treaty-Making Powers of International Organizations - Gadkowski, Andrzej (PRAWO i WIĘŹ, 2026)
The aim of this study is to present the nature of the treaty-making powers of international organizations, with particular emphasis on their implied treaty-making powers. While the attributed powers expressly granted in the constitutional instrument of a given international organization raise few doubts, implied powers – which are a special category of attributed powers – require a complex implication process, often based on uncertain foundations, and therefore attract far more criticism. Implication of powers nevertheless allows the interpretation of attributed powers to be more dynamic, which is especially important given the constantly developing activity of international organizations in areas that fall outside of the scope of their statutes. Given the special character of this category of treaty-making powers of international organizations – particularly the questions concerning their nature and the basis for the implication – the author examines this issue in the broader context of the capacities and powers of international organizations. This important topic has not yet been thoroughly addressed in the Polish literature of international law.